An assessment of the English language competence of UPVCC first year students, AY 2001-2002 - Tio, Lilia T.; Espiritu, Belinda P.; Bautista, Dianne Carrol T. (Iloilo City UP Visayas, 2004)
"Assessing the English language proficiency of first year students in UP Cebu College was prompted by the perceived and demonstrated lack of competencies in English by the students. The results revealed that the students generally fared poorly in the Language Competence TEst with a median overall score of 49%, 60% being the modal passing rate in the UP system. Oral sociolinguistic competence was identified as an area of strength; while vocabulary, prepositions, sentence structure, discourse competence, reading comprehension, and written socio-linguistic competence were identified as areas of weakness. The latter, therefore, have to be given priority in the teaching of Communication Skills I not only by the conscious learning of the rules of grammar but also by adequate exposure to language input and application of language skills through extensive reading and writing."
Keywords: University of the Philippines Cebu College (UPCC).; English language -- Performance; English language competencies